Penggunaan Semivariogram pada Metode Ordinary Kriging untuk Mengestimasi Curah Hujan di Kabupaten Kuantan Singingi - Esil Metra; Dewi Murni (Journal of Mathematics UNP, 2023)
In a measurement of  rainfall data, not all points are gauges because of a limitation. So the Meteorology, Climatology and Geophysics Agency (BMKG) only builds rain gauge posts in areas considered to have potential and can represent the surrounding area. Given these limitations, a method is needed to estimate rainfall data outside the observation post area, namely a geostatistical method called ordinary kriging. Ordinary Kriging is a method for estimating a non-sampled value based on the sampled values around it. By using an experimental semivariogram model compared to several theoretical semivariograms (Exponential, Gaussian, and Spherical) and selecting one of the best semivariogram models to estimate the value to be searched, so that optimal estimation results are obtained. In this study, estimated rainfall in Kuantan Singingi Regency in February 2023 where the results obtained are the average rainfall in each sub-district, which is 220.3827 mm, while the estimated rainfall in each village is 217.180. So that Kuantan Singingi Regency is an area with moderate rainfall.